2023
DOI: 10.1093/europace/euad269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in-hospital outcomes and complications of leadless pacemaker and traditional transvenous pacemaker implantation

Majd Al Deen Alhuarrat,
Amrin Kharawala,
Sarath Renjithlal
et al.

Abstract: Introduction Since their introduction in 1958, traditional cardiac pacemakers have undergone considerable upgrades over the years, but they continue to have a complication rate of around 3.8% to 12.4%. There are no randomized controlled trials comparing outcomes of leadless pacemakers (LPM) with single chamber transvenous pacemakers (TV-VVI). Objective Assess the differences in the procedural complications and in-hospital out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This range is consistent with prior studies that have reported an incidence of LP-associated thrombus ranging from 0.2% to 4.2%. 2,9,10 In our cohort, the clinical importance of a numerically higher incidence of device-associated thrombus is unclear but serves as the basis for our conclusion that heparin bolus should still be considered in long cases or high-risk patients.…”
Section: Discussionmentioning
confidence: 94%
“…This range is consistent with prior studies that have reported an incidence of LP-associated thrombus ranging from 0.2% to 4.2%. 2,9,10 In our cohort, the clinical importance of a numerically higher incidence of device-associated thrombus is unclear but serves as the basis for our conclusion that heparin bolus should still be considered in long cases or high-risk patients.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have highlighted safety and efficacity, supporting their utilization [ 22 ]. However, recent findings underscore potential concerns, with evidence suggesting higher inhospitality rates compared to traditional transvenous devices [ 23 ]. Given these conflicting findings, larger randomized trials are essential to elucidate the true benefits and risks associated with the use of leadless pacemakers in this setting.…”
Section: Discussionmentioning
confidence: 99%